DE FUNCIONÁRIO A SERVIDOR, NAS TRAMAS DOS SABERES: práticas discursivas na fabricação do funcionário público estadual maranhense. - MARQUES, Maxhemyliano Silva (2018)
What’s the meaning of being/performing a subject? When we think about this question, we see the subject as a historical drawing which only exists socially in the bosom of language social practices that determine how to be and how to exercise it. Confronted with the philosophical question above, to whose a nswer we resort to Michel Foucault’s postulates on power and knowledge constitution, we present this study whose object is the state government public officer aiming at understanding how two institutions (the government of the state of Maranhão and a union of civil servants) and two nonunionized public officers produce, within their language practices, the meanings of being a public officer in the state of Maranhão. We start from the initial problem that the public officer is a scientific object to fields s uch as Public Administration and Law. So, from a genealogical perspective these knowledges conditioned the production of certain evidences so as to make natural the meaning of being a public officer. W e set out on Foucault’s ( 1968; 1972; 1975; 1984; 1995; 1997; 1998; 2004; 2006a; 2006b) archaeogenealogic venture to describe an archive that constitutes what it is to be a public officer in Brazil. We also anchor this study on the position of some Brazilian researchers such as Gregolin (2003; 2004a; 2004b; 200 5; 2006), Navarro (2004; 2008; 2015), Sargentini (1997; 2006; 2012), Silva (2004), among other researchers of the Brazilian Discourse Studies. By constituting an archive that rescues the sayability regimes about this subject within the dispersion of know ledge of a historical flow characterized by discontinuity, we define of the corpora of our research. In the same timeline we selected statements from the state government of Maranhão (2015 - 2016), from the main union of state public officers (SINTSEP), an d voices of nonunionized public officers. We resorted to materialities that take as object the current conditions in which the public officers of the state of Maranhão perform their public functions. Within this dispersion we attempted to analyze regularit ies of the effects of meaning that arise from the formulations of these three social speech contexts. We analyzed the effects of memory in relation to the archive that these statements make use of or even displace in their production of meanings. For this, we confronted the formulations that make up our corpus with the archive, highlighting the position of the statements analyzed within it. In our analyzes we understand that the historical moment, namely the economic crisis, constitutes the formulations of the two institutions analyzed, and of the nonunionalized subjects, who even referring to the same object, discursively make different subjects. We also notice that the truths about the subjects of our study are unstable: they are spread out to meet the nee ds of those who exercise power.